Teaching CAD/CAM as Major Subject at Technical College - Ngo, Anh Tuấn (Journal of Technical Education Science, 2012)
By looking at teaching CAD/CAM as practicing in an industrial system we can use pedagogical methods from the well-developed discipline organization. Practicing in an industrial system breaks a complex field down into attainable steps, showing how learning strategies and attitudes can enhance mastery. Balancing the realistic emphases of organizational analysis, communicative intent and contextual application can address different learning styles. Guiding students in learning approaches from systematic study will equip them to deal with constantly changing technology. Practicing learning strategies on realistic projects provides the ability to connect concepts to actual situations, drawing on resource-usage, task management, and problem management skills. Including collaborative aspects in these projects provides the motivation of a real audience while linking academic study to practical concerns.